Assessment of factors affecting student’s satisfaction and loyalty on the crossed parking system at residential colleges of Universiti Kebangsaan Malaysia - Siti Khairunisa Zainal,; Amiruddin Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2019)
An increase in the number of students studying in Universiti Kebangsaan Malaysia (UKM) (the National University of Malaysia) has led to increase parking facilities requirements at residential colleges. Some colleges applied crossed parking systems to address these problems. This study aims to ensure that parking facilities provided at UKM’s residential colleges are adequate in the future and explaining the impact of parking services on the satisfaction and loyalty of students. The primary data was obtained by calculating the parking turnover and questionnaire survey. Secondary data is obtained from the college’s management that implement cross parking systems, namely Keris Mas College (KKM), Rahim Kajai College (KRK) and Pendeta Zaaba College (KPZ). This study has two models, the model of adequacy level of parking facilities at college and parking service quality model on student satisfaction and loyalty. This study applies the SERVQUAL and Loyalty models. Then, observation data will be analysed using EXCEL and parking plans drawn using AUTOCAD. Questionnaires were analysed by the SEM method using SPSS and AMOS Graphic software. Observation studies produce several features and behaviours of crossed parking systems. The peak hours for KKM, KRK and KPZ start at 5.00 pm-8.00 am, 10.00 pm- 7.00 am and 6.00 pm-8.00 am where the number of vehicles exceeds the parking space provided. The maximum number of parking vehicles outside the bar and in the prohibited areas for KKM, KRK and KPZ are 134 and 25, 30 and 3 and 84 and 10 vehicles. This situation shows that crossed parking facilities provided are inadequate and at critical levels. Meanwhile, the questionnaire survey shows that the main determinants of parking services quality are tangible, reliability and assurance factor. These factors have a significant impact on service quality. Determinants that not significant which are reliability, responsiveness and empathy have been ignored. Finally, the respondents were dissatisfied with this parking system and refused to propose their friends to park vehicles in the crossbar area.